Dark Fantasy Aesthetics in Indonesian Animation: Visual Analysis and Character Representation in the Film Panji Tengkorak - Imamul Masyhudi; Rifki Risandhy (ULTIMART Jurnal Komunikasi Visual, 2026)
The animated film Panji Tengkorak (2025), produced by Falcon Pictures, presents a distinctive visual approach within the development of Indonesian animation through its application of dark fantasy aesthetics and a narrative aimed at adult audiences. This study aims to analyze the construction of dark fantasy visual aesthetics and the reinterpretation of the traditional Indonesian jawara figure as represented through the visual attributes of the main character. The research uses a descriptive qualitative approach using formalist aesthetic analysis and Roland Barthes’ visual semiotics. The research data consist of 12 visual ex-cerpts (film stills) selected through purposive sampling based on their relevance to elements of color, lighting, visual texture, character attributes, and the main narrative conflict. The findings reveal that the dominance of an earth-tone color palette, chiaroscuro lighting, and rough visual textures creates a dark fantasy atmosphere characterized by gloom and psychological tension. The semiotic analysis indicates that the character’s visual attributes, including the skull mask, clothing and bodily scars, and weaponry, generate denotative, connotative, and mythical meanings that represent the jawara figure as a traumatized survivor, socially alienated, and morally ambiguous individual. These findings demonstrate that visual aesthetics function not only to establish narrative atmosphere but also to reconstruct the meaning of heroism within the context of contemporary Indonesian popular culture.